1988
DOI: 10.1016/0735-1097(88)90397-x
|View full text |Cite
|
Sign up to set email alerts
|

Early recovery of left ventricular function after thrombolytic therapy for acute myocardial infarction: An important determinant of survival

Abstract: Thrombolytic therapy for acute myocardial infarction reduces early mortality, but full recovery of left ventricular function after reperfusion is delayed. Therefore, the relations among reperfusion, survival and the time course of left ventricular functional recovery were examined in 226 patients treated with intracoronary streptokinase; 77% (134 patients) had sustained reperfusion and 31 patients had no reperfusion or had reocclusion by day 3. Wall motion was measured from contrast ventriculograms performed i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
53
1
1

Year Published

1989
1989
2005
2005

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 188 publications
(56 citation statements)
references
References 53 publications
0
53
1
1
Order By: Relevance
“…Improvement in ventricular function occurred gradually over the course of a few weeks. [81][82][83][84] One report 85 suggested that stunned myocardium could be recruited after thrombolytic therapy with small boluses of inotropes. These studies suggest that the ultimate return of cardiac function cannot be determined immediately after reperfusion.…”
Section: Myocardial Stunning In Humansmentioning
confidence: 99%
“…Improvement in ventricular function occurred gradually over the course of a few weeks. [81][82][83][84] One report 85 suggested that stunned myocardium could be recruited after thrombolytic therapy with small boluses of inotropes. These studies suggest that the ultimate return of cardiac function cannot be determined immediately after reperfusion.…”
Section: Myocardial Stunning In Humansmentioning
confidence: 99%
“…Early in the thrombolytic era, it became clear that, as had been observed in the case of myocardial salvage in the canine model, benefit was greatest when such therapy was initiated within 1 hour of symptom onset. 8,10,13,15 As originally conceived, thrombolytic therapy was intended to interrupt the progression from myocardial ischemia to necrosis that resulted from occlusion of the infarct-related artery (IRA) (Fig 1) [19][20][21] This modest improvement in LVEF induced by reperfusion is due to the preservation of regional myocardial function in the distribution of the IRA. 21 Like patient survival, the extent to which thrombolysis preserves left ventricular function depends on the time interval between the onset of symptoms and commencement of treatment.…”
Section: Current Perspectives Potential Benefits Of Late Reperfusion mentioning
confidence: 99%
“…8,10,13,15 As originally conceived, thrombolytic therapy was intended to interrupt the progression from myocardial ischemia to necrosis that resulted from occlusion of the infarct-related artery (IRA) (Fig 1) [19][20][21] This modest improvement in LVEF induced by reperfusion is due to the preservation of regional myocardial function in the distribution of the IRA. 21 Like patient survival, the extent to which thrombolysis preserves left ventricular function depends on the time interval between the onset of symptoms and commencement of treatment. [19][20][21][22][23][24][25] The sequence described above, ie, early reperfusion of an occluded IRA -* myocardial salvage --preservation of regional function --preservation of global left ventricular function -> improved patient survival, is supported by many experimental and clinical studies and has become so widely accepted that it could be called a "paradigm."…”
Section: Current Perspectives Potential Benefits Of Late Reperfusion mentioning
confidence: 99%
See 1 more Smart Citation
“…Early assessment of regional function within the infarct zone appears to be of limited clinical value10U11; however, function of the noninfarct zone may be predictive of hemodynamic status12 and survival. 10,13 Likewise, the presence of multivessel coronary disease has been associated with a high mortality after acute myocardial infarction.14 Whether this increased mortality is due to large infarction size, suppression of compensatory hyperkinesis in the noninfarct zone, or a combination of these factors has not been investigated. A better understanding of the pathophysiology of myocardial function remote from the infarct zone could lead to strategies enabling maximization of global ventricular function.…”
mentioning
confidence: 99%